Early bacterial identification and carbapenemase detection from positive blood culture by mass spectrometry and Blue-Carba test - Cattani, María Eugenia; Cogut, Sandra; Kaufman, Sara C. (The European Research Journal, 2020)
Objectives: In this study, we evaluated a rapid and simple protocol for direct identification of microorganisms with Matrix-Assisted Laser Desorption/Ionization Time of Flight, Mass Spectrometry (MALDI-TOF MS) after a short incubation in solid medium (3 to 5h).Methods: We have examined a total of 1101 positive blood culture bottles from 782 patients.Results: We obtained a correct identification in 1037 (94.18%); 190 (98.44%) were Staphylococcus aureus, and 386 (98.44%) Enterobacteriaceae. Both are the most frequent etiological agents of sepsis. A total of 1004 bottles were monomicrobial (96.81%) and 33 (3.18%), polimicrobial. In the latter we identified at least one species. Two hundred eighty (27.00%) organism isolated were considered skin contaminant. Carbapenemase tests were performed with Blue-Carba test in 140 patinas from Gram negative bacilli, we have detected earlier 27 of 29 positive (93.10%). Conclusions: Mass spectrometry by MALDI-TOF MS is very useful to quickly identify the microbial agent and Blue-Carba contribute to adapt the antibiotic therapy to obtain a correct clinical management of the patient with bacteremia.